ANALYSIS OF FLOOD DISASTER POTENTIAL IN THE SAUKOREM AREA, AMBERBAKEN REGENCY, TAMBRAUW REGENCY, SOUTHWEST PAPUA PROVINCE: ANALISIS POTENSI BENCANA BANJIR DI DAERAH SAUKOREM DISTRIK AMBERBAKEN KABUPATEN TAMBRAUW PROVINSI PAPUA BARAT DAYA - warijo, alfons; Mayzarah, Erikha M. (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2024)
Floods are hydrometeorological disasters that frequently occur in Southwest Papua Province, including Tambrauw Regency. This research was conducted in January – July 2024 in Saukorem Village, Tambrauw Regency, West Papua Province. The research area is located at the coordinates 0° 34' 00